1999
DOI: 10.1111/j.1749-6632.1999.tb09458.x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis of Published Studies Concerning the Validity of Thoracic Impedance Cardiography

Abstract: TIC might be useful for trend analysis of different groups of patients. However, since the reference method was of significant influence, differences between TIC and the reference method are incorrectly attributed to TIC alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 10 publications
1
23
0
1
Order By: Relevance
“…These are well validated but usually require specialized equipment such as a customized mass spectrometer to measure breath-by-breath gas uptake, and may not be feasible for all laboratories. Simpler, non-invasive ways to estimate cardiac output include the arterial waveform analysis and transthoracic impedance (9, 61, 82, 113). These need to be used with care and are frequently best applied to evaluate changes within a subject during acute interventions rather than absolute values.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…These are well validated but usually require specialized equipment such as a customized mass spectrometer to measure breath-by-breath gas uptake, and may not be feasible for all laboratories. Simpler, non-invasive ways to estimate cardiac output include the arterial waveform analysis and transthoracic impedance (9, 61, 82, 113). These need to be used with care and are frequently best applied to evaluate changes within a subject during acute interventions rather than absolute values.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Several studies have shown IC to be a more reliable and effective method of monitoring systolic time intervals than arteriography [6]. Meta-analysis of published literature on the validity of IC-derived measures showed a pooled correlation coefficient of 0.84 for repeated measurement for CO for healthy people [9]. Correlations for 1-week temporal stability during subtraction, handgrip and drawing task sessions in children ranged from 0.81 to 0.86 for heart rate (HR), from 0.88 to 0.93 for PEP, from 0.77 to 0.85 for LVET, from 0.79 to 0.89 for Heather Index (HI), from 0.82 to 0.86 for stroke volume (SV), from 0.77 to 0.81 for CO, from 0.60 to 0.75 for systolic blood pressure (SBP), from 0.13 to 0.61 for diastolic blood pressure (DBP), from 0.28 to 0.67 for mean arterial pressure (MAP) and from 0.69 to 0.78 for total peripheral resistance (TPR) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic impedance cardiography has been used for the measurement of CO noninvasively in PAH, 18 and its reliability was shown to be compromised in cardiac patients in a meta-analysis. 19 We demonstrated strong correlations among the NICaS, TD, and the Fick methods for the measurement of CO. Although the limits of agreement between NI-CO and TD-CO or Fick-CO estimated by the Bland-Altman approach were not small, they were acceptable when compared with previous reports.…”
Section: Discussionmentioning
confidence: 99%